PERSEPSI NILAI DAN RISIKO TERHADAP NIAT PEMBELIAN ULANG DENGAN RASA PERCAYA SEBAGAI VARIABEL MEDIASI PADA PRODUK PENDINGIN RUANGAN RAMAH LINGUNGAN - Tri Budi Prasetyo (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2016)
public awareness on the issue of environmental pollution from the company's activities to be very important. Public concern for the environment has grown rapidly and become a major issue as a result of global warming, many companies that pay attention to the use to explore the green surroundings. Result: The perception of the value of a positive effect on repeat purchase intention; risk perception negatively affect repeat purchase intention; confidence can mediate perfect (perfect mediation) perception of the value of the repeat purchase intention; confidence can run private mediate partial (partial mediaton) perception of risk to re-purchase intention; and confidence positive effect on repurchase intention. Suggestions for further research: the research done on the manufacturing industry products and services; subsequent studies add some other mediating variables that can be studied as the locus of control both LOC internal and LOC external. Limitations of the study: the lack of information provided by the manufacturer or sales in environmentally friendly air conditioning products; lack of knowledge of respondents would impact caused by cooling the room. Keywords: Value Perception, Risk Perception, Repurchase Intention, Trust